Modal Manusia : Pendidikan, Kesehatan dalam Pembangunan Ekonomi - SAFITRI, VIVI (Salam (Islamic Economics Journal), 2022)
This study aims to determine the importance of education and health in economic development. Errors in education in Indonesia are a problem that must be resolved. So that education can be realized as for economic development in Indonesia, and vice versa with health. Health is important for economic development. If many of the population is unhealthy, the country will become poor, therefore the role of the government is to provide health services for its citizens in order to realize prosperous economic development. Keywords: Modal Manusia : Pendidikan Kesehatan dalam Pembangunan Ekonomi